How Does the Trajectory of Multimorbidity Vary Across Black, White, and Mexican Americans in Middle and Old Age? - Quiñones, Ana R. (Oxford University Press, 2011)
OBJECTIVES. This research examines intra- and interpersonal differences in multiple chronic conditions reported by Americans aged 51 and older for a period up to 11 years. It focuses on how changes in multimorbidity vary across White, Black, and Mexican Americans. METHODS. Data came from 17,517 respondents of the Health and Retirement Study (1995–2006) with up to 5 repeated observations. Hierarchical linear models were employed to analyze ethnic variations in temporal changes of reported comorbidities. FINDINGS. Middle-aged and older Americans have on average nearly 2 chronic diseases at the baseline, which increased to almost 3 conditions in 11 years. White Americans differ from Black and Mexican Americans in terms of level and rate of change of multimorbidity. Mexican Americans demonstrate lower initial levels and slower accumulation of comorbidities relative to Whites. In contrast, Blacks showed an elevated level of multimorbidity throughout the 11-year period of observation, although their rate of change slowed relative to Whites. DISCUSSION. These results suggest that health differences between Black Americans and other ethnic groups including White and Mexican Americans persist in the trajectory of multimorbidity even when population heterogeneity is adjusted. Further research is needed concerning the impact of health disadvantages and differential mortality that may have occurred before middle age as well as exploring the role of nativity, the nature of self-reported diseases, and heterogeneity underlying the average trajectory of multimorbidity for ethnic elders.